Family as a redistributive principle of welfare states: An international comparison. (February 2023) - Frericks, Patricia; Gurín, Martin
Redistribution is one of the main characteristics of the welfare state, and welfare state research has dealt intensely with various facets of it. The main focus in analysing redistribution is on the redistributive logics of welfare states in terms of work-related rights. Family as a major principle of welfare state redistribution, though, has hardly been included in these welfare state analyses. It has mainly been addressed by analysing outcome data or by analysing care as the most relevant characteristic of the family. We argue, though, that comparative welfare state analysis that addresses differences in welfare state intended redistribution needs to also include family as a redistributive principle to gain a more complete picture of societal redistribution. In this study, we are analysing the redistributive logics of welfare states in terms of family. We answer the question of how and in how far welfare states institutionalize family as a redistributive principle. We examine by means of the tax–benefit microsimulation model EUROMOD and its Hypothetical Household Tool (HHoT) welfare state regulations on family for three countries that are generally classed as different regime types. We differentiate between a great variety of family forms (referring to marital status, children and different forms of couples' income distribution) to adequately test our theoretical assumptions. The findings show that family is a major redistributive principle of the welfare states analysed here and applied in different redistributive logics to the various family forms. This, then, results in an increase in income for certain family forms and a decrease in income for other family forms. These differences are not the result of one coherent set of regulations, but of an interplay of in part contradictory regulations that reflect a great variety of family-related redistributive logics within the single countries. Thus our study provides new insights into the redistributive logics of welfare states, and may contribute to the analysis of welfare state complexity in terms of theory, methodology and empirics.